SYNTHESIS AND COMPLEXATION PROPERTIES OF A NOVEL POTASSIUM-SELECTIVE TRISANISYL BIS(BENZO-CROWN ETHER) - Beer, P; Tite, E; Ibbotson, A (1990)
The condensation of 2,2′2″-trimethoxy-5,5′,5″- trimethyl-1,1′:3′,1″-terphenyl-3,3″-di(carbonyl chloride) (2) with two equivalents of 4-aminobenzo-15-crown-5 (15-amino-2,3,5,6,8,9,11,12-octahydro-1,4,7,10,13-benzopentaoxacyclopentadecine) (3) gave a novel bis(crown ether) (4) containing a rigid preorganised trisanisyl chain backbone. Titrations of this new host with alkali-metal cations and the ammonium ion monitored by 13C n.m.r. spectroscopy suggested that the benzo crown ether moieties alone provided the co-ordinating sites for the cationic guests, forming a 1:2 [(4):M+] complex with sodium ions, while potassium, rubidium, and ammonium ions formed 1:1 intramolecular sandwich complexes. The association constants (K/dm3 mol-1) of the bis(crown ether) (4) with picrate salts of potassium (7.93 × 10 6), rubidium (0.19 × 106), caesium (0.03 × 106), and ammonium (0.02 × 106) in CDCl3 were measured by deuteriochloroform-water extraction and spectroscopic techniques, indicating a high degree of selectivity for potassium over the other cations [K(K+)/K(Rb+) = 42, K(K+)/K(Cs +) = 264, and K(K+)/K(NH4+) = 397]. This result is in agreement with fast-atom-bombardment mass spectrometric competition experiments.